Measurement of air pollution in Norilsk - フカサワ, タツヤ; オオタ, サチオ; エノモト, キョウイチ; ムラオ, ナオト; ヤマガタ, サダム; シミズ, タツオ; /; Fukasawa, Tatsuya; Ohta, Sachio; Enomoto, Kyoichi; Murao, Naoto; Yamagata, Sadamu; et al. (National Institute of Polar Research, 2000)
P(論文) Air pollution, deposition and its accumulation in surface soil were investigated in Norilsk, Russia. Concentrations of SO_2 and NO_2 gas were measured in Norilsk by using passive samplers 29 July-4 August 1993 and 31 July-4 August 1995. SO_2 concentrations were more than 100ppb in downtown Norilsk; the highest value was 260ppb in 1995. On the other hand, NO_2 concentrations were rather lower than those in Sapporo, Japan. Aerosol chemical species were continuously measured from summer 1993 to summer 1995 at Norilsk Experimental Center in downtown Norilsk. Major components of aerosol chemical species were sulfate (0.9-16μgm^<-3>), organics (1.6-12μgm^<-3>) and elemental carbon (0.1-4.2μgm^<-3>). The ranges of heavy metal concentrations (ng m^<-3>) were Cu, 2-300; Pb, 0.5-83 and Ni, 1-48 with no significant seasonal variations, about ten times more than those in Sapporo. We also collected larch needles, mosses and soil samples to evaluate the deposition and accumulation of the air pollutants. The concentrations of heavy metal and sulfate in larch needles, mosses and surface soil samples decrease with distance from the center of Norilsk. Heavy metal concentrations in deep soil (20-30cm) were nearly equal to the global mean, whereas the concentrations in surface soil (5-10cm depth) were several times to hundreds times higher than those in deep soil (20-30cm depth). This suggests that the emitted pollutant has been deposited and accumulated in surface soil for 40 years, since the nickel-copper smelting companies started operations. departmental bulletin paper